2018
DOI: 10.4236/oalib.1104770
|View full text |Cite
|
Sign up to set email alerts
|

A Review and the Length-Weight Relationship of Bluefish, Pomatomus saltatrix (Linnaeus, 1766), Pisces: Pomatomidae, at the Marine Extractive Reserve (RESEX-Mar) of Arraial do Cabo, Rio de Janeiro State, Brazil

Abstract: The bluefish, Pomatomus saltatrix (Linnaeus, 1766), the only representative of the Pomatomidae family, is a key fishing resource that represents a substantial part of the landings at RESEX-Mar of Arraial do Cabo-RJ. The species is broadly distributed throughout the continental shelf in tropical and warm temperate waters of the Atlantic, Pacific and Indian Oceans. It forms pelagic, large and fast moving shoals in relatively deep offshore waters, and draws close to the coast when temperatures reach from 12˚C to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
0
0
Order By: Relevance
“…Such comparisons indicated that the value of the slope b varies between 2.509 (negative allometric growth) and 3.330 (positive allometric growth) including the results of this study. Cumplido et al (2018), working within the same region in the southeastern coast of Brazil, observed b values similar to those reported here, despite the fact that their size range included smaller fishes. This negative allometric growth pattern (b = 2.55) was slightly smaller than that observed for the southern coast of Brazil (b = 3.05, positive allometric growth) (Bernardes, Rossi-Wongtschowski, 2000;Haimovici, Velasco, 2000), slightly higher than the Mediterranean (b = 2.52) (Bok et al, 2011), and the middle Brazilian coast (b = 2.50, negative allometric growth) (Frota et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Such comparisons indicated that the value of the slope b varies between 2.509 (negative allometric growth) and 3.330 (positive allometric growth) including the results of this study. Cumplido et al (2018), working within the same region in the southeastern coast of Brazil, observed b values similar to those reported here, despite the fact that their size range included smaller fishes. This negative allometric growth pattern (b = 2.55) was slightly smaller than that observed for the southern coast of Brazil (b = 3.05, positive allometric growth) (Bernardes, Rossi-Wongtschowski, 2000;Haimovici, Velasco, 2000), slightly higher than the Mediterranean (b = 2.52) (Bok et al, 2011), and the middle Brazilian coast (b = 2.50, negative allometric growth) (Frota et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…The presence of more than one event of spawning and recruitment were already observed in other populations of P. saltatrix (Hare & Cowen, 1996; Ward et al., 2003). In the South region, the spawning season occurs during the summer (Haimovici & Krug, 1996; Krug & Haimovici, 1991; Muelbert & Sinque, 1996) whereas in the Southwest region, the spawning season extends to autumn (Cumplido et al., 2018; Silvano & Begossi, 2010). The maintenance of this divergent scenario could also be explained by a strong philopatry of individuals to reproduce in specific latitudes, combined with spawning closer to the coastline and consequent less dispersion of larvae and recruits.…”
Section: Discussionmentioning
confidence: 99%
“…The species seems to have peaks of migrations and reproduction in late spring to summer, in regions between south Brazil and Argentina (30–40° S, 50–60° W) (Haimovici & Krug, 1996). Higher abundance of bluefish with larger sizes and mature gonads were also documented in the summer and autumn in southeastern Brazil (São Paulo and Rio de Janeiro coasts: 22–24° S, 41–45° W) (Cumplido et al., 2018; Silvano & Begossi, 2010), regions that are 1600 km apart from the southern ones. This discontinuous pattern in spawning regions has the potential to generate population divergences, and consequently, distinct fishery stocks (Lund Jr & Maltezos, 1970).…”
Section: Introductionmentioning
confidence: 91%